Development of rapid label-free cells discriminator for dengue-infected hepatic cells utilizing dielectrophoresis / Bashar Mohammed Shaher Yafouz - Bashar Mohammed, Shaher Yafouz (2016)

(untitled)
This thesis presents the development of a label-free cell discriminator for dengue-infected cells using Dielectrophoresis (DEP). DEP, the induced movement of dielectric particles in a non-uniform electric field, has been used as a potential technique for the manipulation and separation of many biological samples without destructive consequences to the cell. Because cells of the same genotype in different physiological and pathological states have unique morphological and structural features, it is possible to differentiate normal and infected cells using their DEP responses. The proposed lab-on-a-chip platform consisted of five layers and employs microarray dot electrodes that utilize both positive and negative DEP effects. The geometry of the electrode design was optimized with numerical modeling using COMSOL Multiphysics 4.2a®. The testing and proof of feasibility for this device were performed by conducting size-dependent manipulation and separation experiments on 1, 5 and 15 μm polystyrene particles. A total of 120 samples (60 samples of normal WRL-68 cells and 60 samples of Dengue-infected WRL-68 cells) were used to conduct the DEP experiments to discriminate between normal and infected cells. The DEP responses of the cells were quantified by analyzing the light intensity shift of the captured images before and after the application of the electric field. The differences in dielectric properties between normal and infected cells were exploited by plotting a unique DEP spectrum for each set of cells and obtaining the DEP crossover frequency at which no resultant movement occurs to the cells in response to the DEP force.